Prevalence, awareness, treatment, control, and treatment-control rates of hypertension among adults in Hubei province: a cross-sectional survey - Tianjing HE; Lan ZHANG; Shuzhen ZHU; Miaoyan SHEN; Qian LI; Yumeng TANG; Mengge ZHOU; Jingju PAN (Zhongguo gonggong weisheng)
ObjectiveTo investigate the prevalence, awareness, treatment, control, and treatment-control rates of hypertension among adults in Hubei province, and to provide a reference for the prevention and control of hypertension in this region. MethodsBlood pressure measurement and face-to-face interview with the Chinese Adult Chronic Disease and Risk Factor Surveillance Survey Questionnaire were conducted during May – December 2020 among 21 973 adult (≥ 18 years) permanent residents recruited using stratified multistage random cluster sampling at 10 counties/districts/prefectures in Hubei province. The participants′ information on hypertension prevalence, awareness, treatment, and control were collected and analyzed. ResultsAmong the 20 286 participants included in the analysis, a total of 8 287 hypertensive subjects were identified and the complex-weighted prevalence of hypertension was 33.3%. Of the 8 287 hypertensive participants, 3 807 (43.1% after complex weighting) were aware of their hypertension, 3 324 (37.2%) were receiving treatment, and 828 (9.2%) had their blood pressure under control. Of the 3 324 hypertensive participants receiving treatment for hypertension, 828 (24.6% after complex weighting) had their blood pressure under control. The complex-weighted prevalence of hypertension among all participants, the complex-weighted ratios of awareness, treatment, and blood pressure control of hypertension among hypertensive participants differed significantly by gender, age, and education (all P < 0.05); the complex-weighted ratio of controlled blood pressure among the hypertensive participants receiving hypertension treatment differed significantly by education level (P < 0.05). The complex-weighted ratios of awareness and treatment among hypertensive participants differed significantly by urban/rural residence (both P < 0.05). ConclusionThe prevalence of hypertension is high among community-dwelling adults in Hubei province, but the awareness, treatment, and control levels of hypertension are low among community-dwelling hypertensive adults.